ANALISIS PENERAPAN PENGADAAN BERKELANJUTAN PADA PT XYZ - Akmalia, Akmalia; Kurniaty, Dewi (LP2M Universitas Bina Bangsa, 2025)
This study aims to improve efficiency in the procurement department by applying the elements of sustainable procurement. The research methodology was carried out with qualitative and observation of documentation studies in the procurement department of PT XYZ. The analysis mechanism is carried out through 3 stages, namely 1) the planning and determination stage where the strategic elements seen are standards, actions and plans, priorities and targets 2) the implementation stage of the strategic elements seen consists of leadership, human resources, communication, finance, knowledge and perceptions, regulations and policies, instruments, processes, participation, support mechanisms, relationships with suppliers and contracts 3) the evaluation stage of the implementation of the strategic elements seen consists of monitoring and reporting. Findings included ineffectiveness in the planning and implementation stages, such as poorly defined priorities and targets. However, focused efforts on improving efficiency, quality and sustainability were seen in supplier selection and cash flow monitoring. Recommendations include improving priority setting and realistic targets, reducing authoritarian leadership, and strengthening HR development and internal coordination. Based on the results from the observation and documentation study at PT XYZ, all elements of sustainable procurement at PT XYZ have been implemented and run effectively. The implications of this finding for the company can be applied as a business strategy planning to ensure a sustainable supply of goods and services, maintain long-term relationships with suppliers at competitive prices, and can improve cost efficiency to optimize expenses, especially in the procurement of raw materials.